Effect of the porosity/cement ratio on the compression of cemented soil - Sara Rios (2012)
The compression behavior of an artificially cemented soil was analyzed by the adjusted porosity/cement index using a correlation established in the recent literature. It was found that for each value of this index, defined as the ratio of porosity to the volumetric cement content, there was a unique normal compression line (NCL). The NCLs of the cemented specimens for each adjusted porosity/cement index did not converge with the NCL of the uncemented silty sand at large stresses, but reached a line parallel to it. The NCL of the cemented sand plotted further from the NCL of the uncemented sand as the porosity/cement index decreased. DOI: 10.1061/(ASCE)GT.1943-5606.0000698. (C) 2012 American Society of Civil Engineers.